2014
DOI: 10.1590/2317-1782/20142014108
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Vocal Program applied to individuals with signals presbylarynx: preliminary results

Abstract: Descritorescoordination between breathing and speaking, accuracy in articulatory movements, jitter, and harmonics-to-noise ratio improved with parameters within the expected range for the age group. Three female participants were observed for better vocal quality, higher fundamental frequency, and better maximum phonation time. In two cases, tension related to loudness elevation and better scores on SPRD was observed. Using by high-speed laryngeal image, we also observed reduction of presbylarynx signs, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
2
10
0
1
Order By: Relevance
“…However, in 1994, this method was simplified to The Roughness, Breathiness, Hoarseness (RBH) Scale through the omission of Asthenia and Strain by Hussein Gaber et al 16 In 2002, another scale called The Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V) was developed by the American Speech-Language-Hearing Association. 17 Perceptual tests have been used for a long time. However, perceptual evaluation has some difficulties, and an experienced staff is mandatory for appropriate application of the test.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 1994, this method was simplified to The Roughness, Breathiness, Hoarseness (RBH) Scale through the omission of Asthenia and Strain by Hussein Gaber et al 16 In 2002, another scale called The Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V) was developed by the American Speech-Language-Hearing Association. 17 Perceptual tests have been used for a long time. However, perceptual evaluation has some difficulties, and an experienced staff is mandatory for appropriate application of the test.…”
Section: Discussionmentioning
confidence: 99%
“…Perception of strain deviation indicated that its values, although small, increased after the voice therapy -a fact probably caused by the progression of intensity that usually develops throughout the therapeutic exercises. Another case report also indicated maintenance of mildly deviant strain in vocal quality (8) . With regards to the pitch parameter, the deviations found demonstrate a tendency of using a slightly higher voice for I1 and a slightly lower voice for I2 after therapy -a fact caused by progression of the exercises with voice frequency.…”
Section: Discussionmentioning
confidence: 92%
“…Studies on the physiological changes of the larynx in the elderly, prevalence of vocal impairments, their vocal quality, and voice involvement in their psychosocial conditions were reported in a literature review (1) . In addition, studies seeking scientific evidence of voice therapy for the elderly have been conducted (2)(3)(4)(5)(6)(7)(8)(9)(10) . The methodologies used in these studies, as well as the sample sizes and interventions applied, varied greatly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies that investigated the acoustic assessment changes in the elderly population immediately after performing a vocal exercise were found. The closer to this was a brief communication about cognitive therapy in three elderly individuals (24) who performed six vocal therapy sessions including different vocal exercises; the outcomes showed improvement in jitter and HNR.…”
Section: Discussionmentioning
confidence: 98%